As produções imagéticas dos livros didáticos de História e a construção do conhecimento discente - (:unkn) unknown (Universidade Federal de Goiás, 2016)
When referring to the production of images contained in the textbooks of history, then we face the difficulties that students feel to interpret, assimilate and be guided by the images that are presented there. A fact noticed in the work done with students in the classroom. To what extent the different imagery materialities conveyed in textbooks are appropriate, integrate or help in the construction of teaching / learning in the history of the area, making it easier the development of knowledge? Objective of this research, investigate and discuss how imagistic presentations are significant and open to interpretation by the student. With the production of textbooks, teachers and students come up against the difficulties to come across a material that does not prioritize their social space, universalizing content, supplementary texts, images, documents and worldviews; a material which did not have access to your building process and that does not meet all students equally; a friendlier learning materials for the publishing industry than concerned with the formation of citizenship and humanization of education. Methodologically, I try to think about and discuss the production and distribution of textbooks, paying attention to the ills surrounding its making and its own building, which is political. Also, try to also discuss the role of this cultural object, as necessary to the teachers and students, whether in their political intentions as in their representations and also think about the different conveyed imagistic materialities in the textbook that can help in the construction of teaching and learning in the area of History thus making it more accessible to develop the knowledge, seeking to make a reflective and critical analysis of experiences situations (everyday images) and teaching-learning, from historical knowledge. For this, we seek support in different authors that address the role of the textbook, as well as being just a teaching support material, but also as an instrument that conveys cultural, political, economic; in authors who discuss the history and social representations; semiotics, as an approach to image analysis; and yet, the authors discuss the Visual Culture, through the study of the visual arts, as props, to understand how our students seek and realize the images around them and in the classroom. All these studies lead to realize that beyond the image there is a plethora of information that often are not present at the scene of an image, but are given as signs, world representations, social meanings and represent a certain period and are represented in time and the historiographical space to which this analyzing. This perception runs through the function only to observe the image; It involves study, discussions and takes the passivity of contemplation and in places with a more dynamic stance, critical front of the work of art study, be it painting, cartoon or charge.
The imagistic production of textbooks of history and construction of student knowledge
Keywords: Produção imagética; Livro didático de História; Ensino aprendizagem; Semiótica; Cultura visual; Image production; Textbooks; Teaching and learning; Semiotics; Visual culture; CIENCIAS HUMANAS::HISTORIA